2003
DOI: 10.1017/s1361491603000133
|View full text |Cite
|
Sign up to set email alerts
|

English commercial banks and business client distress, 1946-63

Abstract: The article examines the behaviour of two leading English clearing banks, the Midland and Westminster, during periods of financial distress suffered by a sample of business clients during the early postwar decades. Such periods provide valuable insight into the nature of bank-business relationships at that time for, in a sense, bank reaction during periods of financial difficulty for client firms helps define the limits to bank support and commitment to such firms. The article examines the banks' behaviour wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…From a historical perspective, often a contrast is drawn between ‘relationship banking’ and ‘transaction banking’. In a system dominated by relationship banking, banks invest a great deal of resources in the collection and monitoring of private information and maintain a close, long-term relationship with business clients; whereas in transaction banking, banks treat each loan as a separate transaction and deal with it on its own merits (Baker and Collins, 2003). This leads us to our second hypothesis:H2: The favourable effects of relationship banking on reducing SME financial problems increase over the level of embeddedness of the relationship with bankers.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…From a historical perspective, often a contrast is drawn between ‘relationship banking’ and ‘transaction banking’. In a system dominated by relationship banking, banks invest a great deal of resources in the collection and monitoring of private information and maintain a close, long-term relationship with business clients; whereas in transaction banking, banks treat each loan as a separate transaction and deal with it on its own merits (Baker and Collins, 2003). This leads us to our second hypothesis:H2: The favourable effects of relationship banking on reducing SME financial problems increase over the level of embeddedness of the relationship with bankers.…”
Section: Hypothesesmentioning
confidence: 99%
“…There is some interesting debate in the literature as to whether such ‘distressed clients’ actually reflect and respond to the advice given by their banks. However, a longitudinal study of the period 1946–1963 revealed that nearly half of distressed business clients received bank advice and intervention in terms of independent investigation and advice on financial structure, change in management and business details (Baker and Collins, 2003). Binks and Ennew (1997) reported that more than 60 percent of small businesses in the UK are willing to provide information to their bank manager, and are positively inclined to discuss excess borrowing in advance.…”
Section: Hypothesesmentioning
confidence: 99%
“…That banks, with senior priority status, do in fact exercise this control when the debtor is financially distressed, in a way that is beneficial for other creditors, is apparent from empirical studies of banks' orchestration of informal rescues (Armour and Frisby, 2001;Baker and Collins, 2003;Franks and Sussman, 2005). Franks and Sussman (2005: 76-77) found that the average firm in their sample of financially distressed borrowers spent seven and a half months with banks' Business Support Units ('BSU's, or colloquially, 'intensive care'), and that (depending on the bank) about somewhere between half to three quarters of these firms emerged from the BSU without going into formal insolvency proceedings.…”
Section: How Is Secured Credit Used?mentioning
confidence: 99%
“…This study found that while the activities of these banks was consistent with the transaction bank model (the dominant paradigm in their earlier, pre-1914 study), it was also the case that in the post-Second World War period these banks were more prepared to exercise an interventionist policy, particularly for their most distressed clients. 47 …”
Section: Accounting Banking and Financial Historymentioning
confidence: 99%